2021
DOI: 10.2147/jir.s306136
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Alveolar Macrophage-Related Core Gene Set in Acute Respiratory Distress Syndrome

Abstract: Purpose Acute respiratory distress syndrome (ARDS) is a rapidly progressive diffuse lung injury that is characterized by high mortality and acute onset. The pathological mechanisms of ARDS are still unclear. But alveolar macrophages have been shown to play an important role in inflammatory responses during ARDS. We aimed to find the biomarkers for ARDS for early diagnosis, to give ARDS patients timely treatment. Methods Gene expression profiles were downloaded from Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…However, the mechanism of action of VAMP8 in carotid atherosclerosis is not clear and the research is not su cient. Then, v-set and immunoglobulin domain containing 4 (VSIG4) promotes the migration of in ammatory cells to the lesion area and participate in the pathogenesis of atherosclerosis by inducing chemokines that activate macrophages [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of action of VAMP8 in carotid atherosclerosis is not clear and the research is not su cient. Then, v-set and immunoglobulin domain containing 4 (VSIG4) promotes the migration of in ammatory cells to the lesion area and participate in the pathogenesis of atherosclerosis by inducing chemokines that activate macrophages [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…VSIG4 may be involved in lung injury through induction of phagocytosis ( 22 ). VSIG4 activate macrophages, through induction of chemokines, promote the migration of inflammatory cells to the lesion area, and participate in the pathogenesis of arteriosclerosis ( 23 ). Increased expressions of C1QA, C1QB, C1QC, and VSIG4 all relate to enhanced complement system.…”
Section: Discussionmentioning
confidence: 99%
“…Immune system function, specifically complement function, has been studied regarding prematurity and sepsis ( 30 , 31 ). Accumulating evidence in the literature has shown that the risk of respiratory distress and genetic background are closely related, and the “gene-host” and “gene-environment” interactions are implicated in the morbidity/mortality associated with this disorder ( 17 , 32 34 ). In this study, we identified for the first time, up to the authors' knowledge, the C1INH rs4926G>A (Val480Met) variant implication in neonatal lung disease risk and outcome in the population under the study.…”
Section: Discussionmentioning
confidence: 99%